A negative photoconductivity photodetector based on two-dimensional Nb3Cl8 - Lee, Bom; Zhang, Xiaojie; Kang, Jinsu; Jeong, Byung Joo; Cho, Sooheon; Choi, Kyung Hwan; Jeon, Jiho; Lee, Sang Hoon; Kim, Dahoon; Kim, Yeong Hyeop; Kim, Ji Hee; Yu, Hak Ki; et al. (Nanoscale, 2024)
Negative photoconductivity (NPC)-based photodetectors offer a new direction for energy-efficient photodetection technologies, featuring low energy consumption and high responsivity. Two-dimensional (2D) materials are particularly promising for implementing NPC due to their large surface area, abundant surface states, and tunable bandgap properties. In this context, 2D Nb3Cl8, with its unique kagome lattice structure and broad absorption spectrum, has attracted considerable interest. Notably, metal halides such as Nb3Cl8 demonstrate significant potential as NPC materials due to their low anionic and cationic bonding strength, which allows for the formation of vacancy defects with high probability. However, the NPC characteristics of Nb3Cl8 have not been thoroughly investigated. In this study, we fabricated field-effect transistors (FETs) using Nb3Cl8 single crystals synthesized via chemical vapor transport (CVT). These devices exhibited an electron mobility of 4.24 × 10−3 cm2 V−1 s−1 and a high Ion/Ioff ratio of 1.42 × 104. Notably, Nb3Cl8-based photodetectors demonstrated consistent NPC behavior across a wide wavelength range of 400-1050 nm, with a high responsivity of 156.82 mA W−1 at 400 nm. We propose that the trapping effect due to defect levels within the bandgap is the primary cause of this NPC phenomenon. The present findings reveal the unique photodetector properties of Nb3Cl8 and highlight its promise in energy-efficient photodetectors and various optoelectronic applications.
Keywords: Bandgap properties; Energy efficient; Kagome lattice structures; Large surface area; Low energy consumption; Photo detection; Responsivity; Tunable Band-gap; Two-dimensional; Two-dimensional materials